EFEITO DE DENSIDADE DE CRIAÇÃO SOBRE AS CARACTERÍSTICAS DE CARCAÇA DE FRANGOS DE CORTE ROSS 308 - SILVA, Maria Vitória,; DE SOUZA, Andréia Fróes Galuci Oliveira,; SILVA, Higor Jonathan de Oliveira,; DA COSTA, Gabriela da Silva da,; DOMINGUES, Elyan Carlos Da Silva,; MARQUES, Ana Leticia Ribeiro, (ANAIS DO ENIC, 2023)
-